Application of technology surveillance tools in the survey of open source technologies that are applicable in the teaching of engineering - Pavlicevic, Juan Santiago (2018)
Nowadays, Information and Communication Technologies (ICT) play a major role in organizations. This is particularly so for universities, that should incorporate ICT to their teaching and management processes, in order to enhance their quality of education. The implementation of open source software should be a priority for universities for a number of features, namely low cost and the possibility to run, copy, modify and distribute the software without limitations, which contributes to collaborative knowledge construction. With regards to technology surveillance, it is a discipline that allows the monitoring and identification of key technologies that, on term, permit the identification of its state of the arts at the global level. This work is an exploratory research on the several forms of open code software that can be applied to the teaching of engineering through the use of technology surveillance tools. The findings hope to contribute to the teaching and learning processes of several training paths for the training courses of the School of Engineering of the Universidad Nacional de Lomas de Zamora (FI-UNLZ).